Assembly of Au Plasmonic Photothermal Agent and Iron Oxide Nanoparticles on Ultrathin Black Phosphorus for Targeted Photothermal and Photodynamic Cancer Therapy. (31st March 2017) - Yang, Dan; Yang, Guixin; Yang, Piaoping; Lv, Ruichan; Gai, Shili; Li, Chunxia; He, Fei; Lin, Jun
Abstract : Photodynamic therapy (PDT), as a minimally invasive and high‐efficiency anticancer approach, has received extensive research attention recently. Despite plenty of effort devoted to exploring various types of photodynamic agents with strong near‐infrared (NIR) absorbance for PDT and many encouraging progresses achieved in the area, effective and safe photodynamic photosensitizers with good biodegradability and biocompatibility are still highly expected. In this work, a novel nanocomposite has been developed by assembly of iron oxide (Fe3 O4 ) nanoparticles (NPs) and Au nanoparticles on black phosphorus sheets (BPs@Au@Fe3 O4 ), which shows a broad light absorption band and a photodegradable character. In vitro and in vivo assay indicates that BPs@Au@Fe3 O4 nanoparticles are highly biocompatible and exhibit excellent tumor inhibition efficacy owing to a synergistic photothermal and photodynamic therapy mediated by a low‐power NIR laser. Importantly, BPs@Au@Fe3 O4 can anticipatorily suppress tumor growth by visualized synergistic therapy with the help of magnetic resonance imaging (MRI). This work presents the first combination application of the photodynamic and photothermal effect deriving from black phosphorus nanosheets and plasmonic photothermal effect from Au nanoparticles together with MRI from Fe3 O4 NPs, which may open the new utilization of black phosphorus nanosheets in biomedicine, optoelectronic devices, and photocatalysis. Abstract : A novel nanoplatform with photodynamic therapy (PDT) and photothermal therapy (PTT) effect is first developed by assembly of iron oxide nanoparticles and Au nanoparticles on black phosphorus sheets, which exhibits excellent tumor inhibition efficacy due to a synergistic PDT and PTT mediated by a low‐power near‐infrared laser, and the therapeutic process can be visualized by magnetic resonance imaging.